Perioperative Nutritional Therapy in Bariatric Surgery: A Case Report - Amelia, Fiona Desi; Christianto, Febe (Journal of Syiah Kuala Dentistry Society, 2024)
Background: Metabolic and bariatric surgery, such as laparoscopic sleeve gastrectomy (LSG), is effective for obese patients with type 2 diabetes mellitus (DM), proven to improve metabolic profiles, control hyperglycemia, and provide DM remission in 55-85% of patients, as well as reducing medication use and body weight (BW) within one year after surgery. Case Report: A 23-year-old female patient with grade II obesity (BMI 31.42 kg/m), DM, and cholecystolithiasis underwent laparoscopic cholecystectomy and LSG. Perioperative clinical nutrition therapy was performed to support the success of the surgery, including BW management, a preoperative diet through the Enhanced Recovery After Surgery (ERAS) protocol, and a gradual postoperative diet from liquid consistency. Evaluation 5 days after surgery showed decreased BW, waist circumference, body fat mass, visceral fat, and HbA1C without complications. The patient was discharged on the 6th day and was advised to adopt a transitional diet, multivitamins, and calcium supplementation. The mechanism of LSG involves calorie restriction, early satiety due to decreased gastric volume, and faster gastric emptying time. Conclusion: Short-term perioperative LSG nutrition therapy aims to meet nutritional needs, support weight loss, and improve metabolic profiles, thus contributing to clinical success for patients with obesity, type 2 diabetes, and metabolic syndrome.